2017
DOI: 10.1080/23723556.2016.1143078
|View full text |Cite
|
Sign up to set email alerts
|

A role for p53 in telomere protection

Abstract: Telomeres cap the ends of chromosomes and are crucial for genome stability. The p53 protein (TP53) is a vital tumor suppressor, activating the transcription of numerous genes in response to cell stress. We reported that direct binding of p53 at human subtelomeres corresponds with local transcription activation and enhanced telomere stability in the presence of DNA damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Loss of function mutations in p53 permit the accumulation of critically short and uncapped telomeres and consequent chromosome instability observed in many p53-mutated cancers. In addition to this canonical pathway, we describe a reciprocal p53-telomere regulation axis mediated through the direct binding of p53 to sequence-specific sites in human and mouse subtelomeres [9, 15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of function mutations in p53 permit the accumulation of critically short and uncapped telomeres and consequent chromosome instability observed in many p53-mutated cancers. In addition to this canonical pathway, we describe a reciprocal p53-telomere regulation axis mediated through the direct binding of p53 to sequence-specific sites in human and mouse subtelomeres [9, 15].…”
Section: Discussionmentioning
confidence: 99%
“…The chromosome regions adjacent to the telomere repeats are referred to as subtlomeres and can also contribute to telomeric chromatin and telomere repeat stability [14]. Subtelomeres can bind to sequence-specific factors and at least one third of human subtelomeres contain high-affinity, sequence-specific p53 binding sites within 10 kB of the telomere repeat track [9, 15]. Subtelomeric binding of p53 stimulates transcription of telomere repeat-encoded RNA (TERRA) and also induces histone acetylation throughout the subtelomeric and telomere repeat region in response to DNA damage signaling [9].…”
Section: Introductionmentioning
confidence: 99%
“…Prior cell-based studies have shown that DNMT3A loss of function increases telomere length, 34 TET2 loss of function decreases telomere length; 35,36 and p53 (TP53) protects telomeres from DNA damage. 37 Thus, we estimated the effect size of each mutated gene on LTL (Fig. 2a, Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Tutton and Lieberman (18) reported that p53 protein is an essential tumour suppressor that activates the various transcription genes involved in cell stress response. p53 direct binding at human sub-telomeres quadrates with activation of transcription and magnifies telomere stability when exists DNA damage (18). Consequently, telomerase inhibitors (or telomere shortening) are now being considered as potential anticancer drugs.…”
Section: Role Of P53 On Telomere Stabilitymentioning
confidence: 99%